Assessing the Impact of Utilization of Dairy and Hospital Waste Waters on Engineering Properties of Concrete. - Bahati, Augustine (Kabale University, 2025)
The hardening of cement gives strength and durability to concrete. The quality of mixing water may affect the setting, hardening, and strength of the concrete. Great control of the properties of cement and aggregates is exercised, but the control of the quality of water is often neglected. The suitability of a particular source of water for making concrete can be checked by casting concrete cubes using water under question and comparing its 7 days, 14 days, and 28 days strength. If the compressive strength is up to 90 percent, the source of water may be accepted. The aim of the present study was to know the effect of chemical, physical,l, and biological parameters in mixing water on different engineering properties of concrete. This work was carried out for a mix of 25-grade concrete to study the effect of the use of Potable (tap water), dairy waste water, and hospital wastewater on the strength development of concrete at 7, 14, and 28 days and fresh concrete properties. From the results, it is observed that Potable water resulted in good strength properties and is more workable compared to dairy and hospital waste water samples. There was also an increase of 29.2% in compressive strength when compared to dairy wastewater and 36.8% when compared with hospital wastewater. Dairy and hospital wastewater samples did not meet the requirements for use in concrete production.